ANALISIS KEWENANGAN KPK RI ATAS PENETAPAN TERSANGKA TINDAK PIDANA KORUPSI MILITER AKTIF PADA LEMBAGA NON MILITER: Analysis of the Authority of the KPK RI on the Determination of Active Military Corruption Suspects in Non-Military Institutions - Syifa Putri Aulia; Setiyono (AMICUS CURIAE, 2025)
Corruption offenses are not exclusively committed by civilians; disciplined military personnel can also be involved. A notable instance of this was disclosed by the Corruption Eradication Commission (KPK) through a sting operation (OTT) on July 27, 2023. During this operation, KPK apprehended several private individuals and the Coordinator of Administration (Koorsmin) of Basarnas RI, Lieutenant Colonel Adm Afri Budi Cahyanto. The identification problem of this analysis is the authority and legal basis for KPK RI to charge the Head of Basarnas RI and the Coordinator of Administration (Koorsmin) of Basarnas RI in the context of the procurement project for disaster victim search equipment. Additionally, it examines the legal foundation for KPK RI to designate an active military officer as a suspect in a corruption case within a non-military institution. The result and conclusion; reveals that KPK possesses the authority to handle corruption cases involving active-duty personnel who are employed in non-military institutions or organizations, even if the perpetrators are active military officers. The primary legal foundation for the Corruption Eradication Commission of the Republic of Indonesia (KPK RI) to designate a suspect in the disaster victim search equipment procurement project is Law Number 19 of 2019, which is the second amendment to Law Number 30 of 2002 on the Corruption Eradication Commission.